Editorial: collagen proportionate area as a prognostic indicator in NAFLD. Issue 11 (10th May 2019) - Ravaioli, Federico; Anstee, Quentin M.
Abstract : Linked Content This article is linked to Buzzetti et al and Buzzetti and Tsochatzis papers. To view these articles, visithttps://doi.org/10.1111/apt.15219 andhttps://doi.org/10.1111/apt.15279 .